Music in the Novel “Point Counter Point” by Aldous Huxley - Liubarets, Nataliia (Pitannâ lìteraturoznavstva, 2013)
The article considers the problem of interaction between word and music in Aldous Huxley’s novel “Point Counter Point”. Music representation in the work is analysed with the use of S. P. Scher’s methodology. His three types of prose musicalization, i.e. word music, verbal music, assimilation of the text to the musical form are traced in the novel at the main levels of text organization. The transposing of the musical method of counterpoint into the narrative structure of the novel is considered in details. Thus, at the thematic level, the theme of death is observed through representing its variations in the storylines of six characters. At the level of narration, the study showed that the technique of constructing micro-monologue by combining two levels of narration causes the effect of simultaneous sounding or non-linear reading. The use of this narrative technique by Huxley’s compatriot and contemporary Virginia Woolf allows regarding it as the experimental one in the scope of modern writing. Perceptions of music by the characters in the novel as well as the author’s ironic attempt to interpret music with the words are regarded as the style creating features of Huxley’s prose. In the conclusion, the deliberate author’s desire for prose musicalization is determined as a modernistic experiment which outlines the prospects of the further study of his works from the viewpoint of intermediality.